Use of intermittent preventive therapy and incidence of acute malaria in pregnancy among postpartum women at University College Hospital, Ibadan, Nigeria (2021)
Background: Malaria in pregnancy remains a significant cause of feto‑maternal morbidity and mortality especially in regions of high prevalence like Nigeria. Intermittent preventive therapy (IPT) for malaria is an important measure to abate this menace. Aim: The aim is to determine the uptake and effectiveness of IPT in relation to the occurrence of malaria, despite the use of IPT in pregnancy. Patients, Materials and Methods: This was a cross‑sectional study conducted in UCH, Ibadan from October 1, to December 31, 2020. A total of 150 postpartum women were selected using the total sampling technique of all consenting participants. Structured questionnaires were used for data collection. Results: About 87.7% of the respondents took IPT in the index pregnancy. Of these, 15.4%, 50.8%, and 33.8% of participants took one, two, and three doses, respectively. The factors that determined intermittent preventive treatment for malaria in pregnancy (IPTp) uptake include occupation (P = 0.001), booking status (P = 0.002), antenatal care attendance (P = 0.001), and level of IPTp awareness (P = 0.002). About 48.0% of respondents indicated that they were treated for malaria in the index pregnancy. Meanwhile, only about 15.3% of those who took IPT were treated for malaria in pregnancy. It was found that the use of IPT (P = 0.03) and an increasing number of IPT doses used (P = 0.03) were associated with a reduction in the prevalence of malaria in pregnancy. Conclusion: The uptake of the current recommendation for IPT‑SP that stipulates the use of monthly doses of IPT till delivery with a target of a minimum of three doses was quite poor. There is therefore an urgent need for widespread awareness and implementation of the World Health Organization and national guidelines on prevention of malaria. The prevalence of malaria declined with the number of doses of IPT‑SP used by the respondents. This emphasizes the need for adequate dosing of IPT.